2020
DOI: 10.1364/ao.405427
|View full text |Cite
|
Sign up to set email alerts
|

Classification of marine microalgae using low-resolution Mueller matrix images and convolutional neural network

Abstract: In this paper, we used a convolutional neural network to study the classification of marine microalgae by using low-resolution Mueller matrix images. Mueller matrix images of 12 species of algae from 5 families were measured by a Mueller matrix microscopy with an LED light source at 514 nm wavelength. The data sets of seven resolution levels were generated by the bicubic interpolation algorithm. We conducted two groups of classification experiments; one group classified the algae into 12 classes according to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…At the same time, the polarized light path need not be designed separately, as long as the current dynamic light scattering light path-polarizing element can be added. At present, it has been applied to biomedicine ( Xiang-Yu et al, 2019 ; He et al, 2021 ; Meng et al, 2021 ; Shen et al, 2021 ; Song et al, 2021 ), marine microbial detection ( Wang et al, 2018 ; Li et al, 2020; Liu et al, 2020 ; Wang et al, 2020 ; Li et al, 2021 ), atmospheric detection ( Li et al, 2019 ; Qizhi et al, 2021 ), etc. It is believed that with the introduction of polarized light technology, the accuracy, measurable parameters, and applicable range of the dynamic light scattering method will be greatly improved.…”
Section: Online Detection Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the polarized light path need not be designed separately, as long as the current dynamic light scattering light path-polarizing element can be added. At present, it has been applied to biomedicine ( Xiang-Yu et al, 2019 ; He et al, 2021 ; Meng et al, 2021 ; Shen et al, 2021 ; Song et al, 2021 ), marine microbial detection ( Wang et al, 2018 ; Li et al, 2020; Liu et al, 2020 ; Wang et al, 2020 ; Li et al, 2021 ), atmospheric detection ( Li et al, 2019 ; Qizhi et al, 2021 ), etc. It is believed that with the introduction of polarized light technology, the accuracy, measurable parameters, and applicable range of the dynamic light scattering method will be greatly improved.…”
Section: Online Detection Of Nanoparticlesmentioning
confidence: 99%
“…Therefore, the development of corresponding detection technology is of great significance to evaluate the properties of nanomaterials and improve the preparation efficiency and quality of nanoparticles. At present, the detection technology mainly focuses on the measurement of macroscopic statistical characteristics and microstructure characteristics of nanoparticles (Liu et al, 2005). The commonly used detection methods can be divided into two types according to the detection principle: (1) the optical-based detection method; (2) the electrical-based detection method; and (3) the mechanical-based detection method.…”
Section: Introductionmentioning
confidence: 99%
“…If the attraction sense for the prey in the hunting region is high, predators employ Brownian method; if not so, if attraction sense of prey is low, Lévy method has been used. Ecological problems such as fish aggregating devices (FADs) effects or eddy formation alternates the marine predator's behavior [19]. In MPA, at first, initial n numbers of population for the prey are defined with considering a lower and an upper bound, i.e.,…”
Section: Marine Predators Algorithmmentioning
confidence: 99%
“…Liu et al. 28 classified marine microalgae using a low-resolution MMIP technique and a CNN and showed that the classification accuracy obtained using the whole Mueller matrix image was greater than that achieved using the image alone at each resolution level. Ma et al.…”
Section: Introductionmentioning
confidence: 99%